Blue zoning the city a comprehensive city-wide model for physical activity to achieve longevity in Laguna - Estrellanes, Gabrelle Noreen A.
Physical inactivity, the fourth leading cause of global mortality, has reduced life expectancy worldwide. Prolonged sedentary behavior significantly contributes to this decline, increasing the risk of chronic conditions like obesity and cardiovascular diseases, thus raising premature death rates. In the Philippines, the PSA reports a life expectancy of approximately 71 years at birth. However, challenges in Laguna, an industrial hub, exacerbate sedentary behavior risks. Inspired by the global Blue Zones where individuals experience enhanced longevity and vitality, this study proposes a methodological framework that identifies issues, collects data through GIS, survey, and interviews, and analyzes it using SWOT, PESTLE, and thematic analyses. These findings inform the development of scenarios aimed at addressing physical inactivity and sedentary behavior risks and promoting longevity in Laguna. The study seeks to introduce a comprehensive city-wide model for physical activity centered on promoting active living, bridging social connections, and enhancing cognitive function of the active population by integrating the principles of the Blue Zones such as Move, Eat Wisely, Connect, and Right Outlook. The proposed development scenarios include Active Common Places, Fitness Infrastructure Development, Nature Park Development, and the Convergence of Developments. The study concludes that the Convergence of Developments is the most promising scenario. This model has the potential to extend life expectancy in Biñan to 97 years and healthy life expectancy to 80 years, underscoring the importance of holistic, community-centric urban planning in promoting longevity and improving the overall quality of life.